PENGARUH LATIHAN ALTERNATE LEG BOX BOUND TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMK LABOR PEKANBARU - Azri, Azri; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research took place at Pekanbaru SMK LABOR. This research was conducted on July 23, 2018 until September 7, 2018 The research method used by the author in this study was the experimental method. The design of this study was a pre-test posttest one group design which was started by doing a pretest Vertical Jump. After that the sample is given an Alternate leg box baund training program for 16 meetings. After that, the Posttest Vertical Jump is done. The data obtained were analyzed descriptively, then the next research hypothesis was tested which had been submitted according to the problem, namely: